Phase II trial of nafamostat mesilate/gemcitabin/S-1 for unresectable pancreatic cancer - Uwagawa, Tadashi; Sakamoto, Taro; Gocho, Takeshi; Shiba, Hiroaki; Onda, Shinji; Yasuda, Jungo; Shirai, Yoshihiro; Hamura, Ryoga; Furukawa, Kenei; Yanaga, Katsuhiko; Ikegami, Toru (PLOS ONE, 2022)
Purpose To assess the efficacy of combination chemotherapy with nafamostat mesilate, gemcitabine and S-1 for unresectable pancreatic cancer patients. Materials and methods The study was conducted as a single-arm, single center, institutional review board-approved phase II trial. Patients received nafamosntat mesilate (4.8 mg/kg continuous transregional arterial infusion) with gemcitabine (1000 mg/m2 transvenous) on days 1 and15, and with oral S-1 [(80 mg/day (BSA<1.25 m2), 100 mg/day (1.25 ≤ BSA<1.5 m2), or 120 mg/day (BSA ≥1.5 m2)] on days 1–14 or, days 1–7 and 15–21. This regimen was repeated at 28-day intervals. Results Forty-seven evaluable patients (Male/Female: 31/16, Age (median): 66 (range 35–78) yrs, Stage III/IV 10/37.) were candidates in this study. Two patients in stage III (20%) could undergo conversion surgery. Twenty-four patients (51%) underwent subsequent treatment (1st line/ 2nd line / 4th line, 13/ 10/ 1, FOLFIRINOX: 12, GEM/nab-PTX: 18, TAS-118: 3, chemoradiation with S-1: 2, GEM/Erlotinib: 1, nal-IRI: 1, surgery: 2). Median PFS and OS were 9.7 (95% CI, 8.9–14.7 mo) and 14.2 months (99% CI, 13.3–23.9 mo), respectively. Median PFS in stage IV patients was 9.2 months (95% CI, 8.4–12.0 mo). Median OS in patients without subsequent treatment was 10.8 months (95% CI, 9.1–13.8 mo). Median OS in patients with subsequent treatment was 19.3 months (95% CI, 18.9–31.9 mo). Grade 4 treatment-related hematological toxicities were encountered in 7 patients. Two patients developed grade 3 allergic reaction after 6 cycles or later. No febrile neutropenia has been observed. Conclusion NAM/GEM/S-1 therapy is safe and could be promising option for unresectable pancreatic cancer, especially for stage IV cancer.